The concept and meaning of landscape in the Malay context. - Maliki, Nor Zarifah (Universiti Sains Malaysia, 2014)
This research aims to understand landscape in the Malay context, mainly through the literatures that very closely describes the Traditional Malay culture. Landscape in a Malay context act as a medium of exchange that evolves within tangible and intangible elements in the Malay societies in its own timeframe.The research has analyzed 4 groups of written materials that contain ideas and descriptions of 'landscape' in the Malay context including classical historical writings, popular writings, idioms and Malay folklores.